Improving the performance of ABR point-to-multipoint connections - Md Shamsuzzaman. (2008)
In this thesis, problems with the existing consolidation algorithms are identified, and a new consolidation algorthm is proposed which overcomes these problems. The results obtained using simulation show that our proposed consolidation algorithm is efficient in terms of scalability, accuracy and responsiveness, and it reduces loss of information related to the consolidation process.